Forest edges have high conservation value for bird communities in mosaic landscapes. Issue 15 (28th June 2016) - Terraube, Julien; Archaux, Frédéric; Deconchat, Marc; van Halder, Inge; Jactel, Hervé; Barbaro, Luc
Abstract: A major conservation challenge in mosaic landscapes is to understand how trait‐specific responses to habitat edges affect bird communities, including potential cascading effects on bird functions providing ecosystem services to forests, such as pest control. Here, we examined how bird species richness, abundance and community composition varied from interior forest habitats and their edges into adjacent open habitats, within a multi‐regional sampling scheme. We further analyzed variations in Conservation Value Index (CVI), Community Specialization Index (CSI) and functional traits across the forest‐edge‐open habitat gradient. Bird species richness, total abundance and CVI were significantly higher at forest edges while CSI peaked at interior open habitats, i.e., furthest from forest edge. In addition, there were important variations in trait‐ and species‐specific responses to forest edges among bird communities. Positive responses to forest edges were found for several forest bird species with unfavorable conservation status. These species were in general insectivores, understorey gleaners, cavity nesters and long‐distance migrants, all traits that displayed higher abundance at forest edges than in forest interiors or adjacent open habitats. Furthermore, consistently with predictions, negative edge effects were recorded in some forest specialist birds and in most open‐habitat birds, showing increasing densities from edges to interior habitats. We thus suggest that increasing landscape‐scale habitat complexity would be beneficial to declining species living in mosaic landscapes combining small woodlands and open habitats. Edge effects between forests and adjacent open habitats may also favor bird functional guilds providing valuable ecosystem services to forests in longstanding fragmented landscapes. Abstract : This study investigates the response of bird communities to habitat edges between woodland patches and open areas in a multi‐region sampling design in French temperate mosaic landscapes. We found that forest edges exhibited higher Conservation Value Index, bird species richness and total abundance. Species sharing life‐history traits expected to be good predictors of vulnerability to global change showed as well a positive response to forest edges. Our results confirmed that forest edges are valuable for conserving and even enhancing biodiversity in managed, fragmented landscapes, by increasing local habitat heterogeneity and mitigating the effects of landscape homogenization linked to modern forestry practices.